MENTAL HEALTH CARE UTILIZATION OF INDIGENOUS PEOPLES IN CANADA (Canadian Journal of Native Studies, 2026)
AbstractThe Indigenous mental health crisis in Canada must be contextualizedwith discussions on race and colonialism within populationhealth research. This research uses nationally representative datafrom the 2015-2016 Canadian Community Health Survey to investigatethe mental health service utilization of Indigenous populations relativeto non-Indigenous populations. Preliminary findings suggest an underutilizationof mental health services by Indigenous people becausealthough they are more likely than non-Indigenous people to possesscharacteristics related to an increased likelihood of consulting a mentalhealth professional, findings show that Indigenous peoples accessmental health services at similar rates as non-Indigenous peoples.